Alteration of Antioxidative Metabolism Induced by Triazoles in Sweet Potato - Alagu Lakshmanan, Pallipalayam Varadharajan Murali and Rajaram Panneerselvam, Thirumal Sivakumar*, Ganapathy Murugan (Journal of Experimental Sciences, 2010)
The triazole induced changes of antioxidants such as ascorbic acid, α-tocopherol, riboflavin, anthocyanin, and xanthophylls and the activities of antioxidant enzymes like ascorbate peroxidase, superoxide dismutase and catalase in Ipomoea batatas L. during initiation and maturation of storage roots were studied in field experiments. Each plant was treated with one liter of aqueous solution containing 20 mg L-1 triadimefon and 15 mg L-1 hexaconazole on 40, 55 and 70 days after planting (DAP). The treatments were given by soil drenching. The plants were harvested on 45, 60, 75, 90 and 105 DAP and used for analyzing antioxidant contents and antioxidant enzyme activities. It was found that these triazole compounds increase the contents of ascorbic acid, α-tocopherol, riboflavin, anthocyanin, and xanthophylls and activities of ascorbate peroxidase, superoxide dismutase, and catalase activities at 105 DAP. Triadimefon and hexaconazole treatments increased the antioxidation status in all parts of plants when compared to the control. -------------------------------------------------------------------------------------------------------- Stress Physiology Lab, Department of Botany, Annamalai University, Annamalai Nagar 608 002, Tamil Nadu, India * Corresponding Author, Email: drtsiva_19@rediffmail.com, Tel: +914144 238248 x354; fax: +914144 222265 Please Cite This Article As: T. Sivakumar, G. M. A. Lakshmanan, P. V. Murali and R. Panneerselvam. 2010. Alteration of Antioxidative Metabolism Induced by Triazoles in Sweet Potato. J. Exp. Sci. 1(3): 10-13.